Individual Field Project Vol. 2: Applying Theoretical Know-How to Real-Life Business and Engineering Situation - Cheng, Jack Kie (Penerbit UMP, 2023)
The Individual Field Project is one of the compulsory courses taken by students of Bachelor of Business Engineering in the Faculty of Industrial Management, Universiti Malaysia Pahang. The purposes of this course are to expose students to real-world settings, and allow students to apply theoretical concepts or tools in solving business and engineering problems. Upon completing this field project, students will gain experience on how to conduct research along with the fundamental processes of academic research writing. Following the tradition of its First Volume, Individual Field Project Volume 2 aims at compiling the case studies written by the students during their field project. This time around, there are 12 different case studies from numerous industries in Malaysia. All the cases were meticulously written with the guidance of respected supervisors from the Faculty of Industrial Management. Despite COVID-19, all students and supervisors have successfully completed the Individual Field Project. Bravo! May your writing be a great reference for future students who will start their very own field projects.